Análisis de costos para la producción de agregados - Guzmán-Gutiérrez, Felipe (Instituto Tecnológico de Costa Rica, 2007)
The aggregate production is an activity that involves many internal and external factors. In the road construction this activity is of extreme importance since from her the materials are derived that compose the structure of pavements. The control and analysis of costs become determining to obtain that the activity is profitable. The inspection in previous site and throughout the process is indispensable to manage to take a daily and representative control of the daily results to analyze the data with time and to make decisions being based on real and opportune facts. Thanks to these procedures we obtained results in certain way favorable having smaller costs to the budgeted ones. Nevertheless we found several internal and external factors that made the activity less profitable. It was fulfilled the expectation to maintain the cost below the budgeted but it was not fulfilled the awaited utility. The costs are affected not only by the machine hours, but also by external factors such as: climate, site of extraction and type of material. The cost is directly related to the productions. The cost is proportional to the production, with greater production, minor the cost and with smaller production greater is the cost.
Proyecto Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2007.
Keywords: Carreteras; Concreto; Análisis de costos; Quebrador; Extracción; Trituración